Layer Structure Preservation during Swelling, Pillaring, and Exfoliation of a Zeolite Precursor - Maheshwari, Sudeep; Jordan, Edgar; Kumar, Sandeep; Bates, Frank S; Penn, R. Lee; Shantz, Daniel F; Tsapatsis, Michael (Journal of the American Chemical Society, 2008)
MCM-22(P), the precursor to zeolite MCM-22, consists of stacks of layers that can be swollen and exfoliated to produce catalytically active materials. However, the current swelling procedures result in significant degradation of crystal morphology along with partial loss of crystallinity and dissolution of the crystalline phase. Fabrication of polymer nanocomposites and coatings with MCM-22 for separation, barrier, and other applications requires a swelling method that does not alter drastically the crystal morphology and layer structure and preserves the high aspect ratio of the layers. Here, we demonstrate such a method by swelling MCM-22(P) at room temperature. The low-temperature process does not disrupt the framework connectivity present in the parent MCM-22(P) material. By extensive washing with water, the swollen material, MCM-22(PS-RT), evolves to a new ordered layered structure. Interestingly, the swelling procedure is reversible and the swollen material can be restored back to MCM-22(P) by acidification of the sample. The swollen material can also be pillared to produce an MCM-36 analogue. It can also be exfoliated, and layers can be incorporated in a polymer matrix to make nanocomposites.